2009
DOI: 10.1007/s00221-009-1757-x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variability in interceptive movements

Abstract: In order to successfully intercept a moving target one must be at the right place at the right time. But simply being there is seldom enough. One usually needs to make contact in a certain manner, for instance to hit the target in a certain direction. How this is best achieved depends on the exact task, but to get an idea of what factors may limit performance we asked people to hit a moving virtual disk through a virtual goal, and analysed the spatial and temporal variability in the way in which they did so. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 35 publications
(37 reference statements)
4
42
1
Order By: Relevance
“…The spatial standard deviation of 2.8 mm is similar to the values found in some earlier studies Smeets 2007, 2011b) but poorer performance has also been reported (Brenner and Smeets 2009). The temporal standard deviation of 8 ms (corresponding to 3.2 mm of target motion) is also better than many estimates of human temporal precision Smeets 2009, 2011b), although slightly more precise performance has also been reported McLeod and Jenkins 1991).…”
Section: Discussionsupporting
confidence: 84%
“…The spatial standard deviation of 2.8 mm is similar to the values found in some earlier studies Smeets 2007, 2011b) but poorer performance has also been reported (Brenner and Smeets 2009). The temporal standard deviation of 8 ms (corresponding to 3.2 mm of target motion) is also better than many estimates of human temporal precision Smeets 2009, 2011b), although slightly more precise performance has also been reported McLeod and Jenkins 1991).…”
Section: Discussionsupporting
confidence: 84%
“…Our results in temporal and spatial precision are not very different from the ones obtained by Brenner and Smeets (2009) for interception tasks. In their experiments subjects saw a disk that moved at 20 cm/s and they had to hit it into a goal while being allowed to see their hand during the whole movement.…”
Section: Discussioncontrasting
confidence: 73%
“…The distinction emerges because performance is only poorer when we block vision for some time between the time that the first prediction can be made and the last moment at which new visual information can lead to useful adjustments. Normally, people will continuously adjust their movements on the basis of continuously updated predictions (Smeets and Brenner 1995;Brenner and Smeets 2009).…”
Section: Discussionmentioning
confidence: 99%